Ciphertext‐Policy Attribute Based Encryption Supporting Any Monotone Access Structures Without Escrow. Issue 3 (1st May 2017) - Zhao, Qianqian; Zhang, Yuqing; Zhang, Guanghua; Wang, He
Abstract : Ciphertext policy attribute‐based encryption (CP‐ABE) is becoming a new primitive for finegrained access control. It neither produces multiple encrypted copies of the same data nor suffers from the severe burden of key distribution and management. The escrow problem that the central authority could decrypt any ciphertexts addressed to all the specific users is still a challenge for CP‐ABE mechanism. One new CP‐ABE scheme without escrow is proposed, and furthermore the proposed scheme achieves fully security in the standard model. The performance and security analysis results indicate that the proposed CP‐ABE scheme is extremely appropriate for cloud storage system.